ANALISIS METODE NUMBERED HEAD TOGETHER TERHADAP KEAKTIFAN BELAJAR SISWA - Magfirotul Fatkha; Ahmad Yuri Alam; Indah Fajarwati (Karimiyah: Journal of Islamic Literature and Muslim Society, 2022)
This study aims to determine whether the application of the NHT (Numbered Head Together) type of cooperative learning model can increase the learning activity of class XII-A students of SMA Nurul Islah in PAI subjects. The type of this research is descriptive qualitative research. The subjects of this research are students of SMA Nurul Islah class XII-A even semester of the academic year 2022/2023 while the object of research is the activity of class XII-A students of SMA Nurul Islah in the subject of Islamic Religious Education. From the results of this research, it is stated that the learning activity of class XII-A SMA Nurul Islah students in PAI subjects using the Number Head Together model has increased. This is shown based on the results of the analysis of the observation sheet, the analysis of the transcription of the video recordings and the analysis of the transcription of the interview recordings of the students, it was concluded that the students were quite active. This can be seen from the analysis of the observation sheet data which says 66.14% of students are quite active to active, and also from the transcription of video recordings that show an active and cooperative learning process in accordance with the Numbered Heads Together method.